Wt-1 Expression Linked to Nitric Oxide Availability during Neonatal Obstructive Nephropathy - Luciana Mazzei; Walter Manucha (Advances in Urology)
The wt-1 gene encodes a zinc finger DNA-binding protein that acts as a transcriptional activator or repressor depending on the cellular or chromosomal context. The wt-1 regulates the expression of a large number of genes that have a critical role in kidney development. Congenital obstructive nephropathy disrupts normal renal development and causes chronic progressive interstitial fibrosis, which contributes to renal growth arrest, ultimately leading to chronic renal failure. Wt-1 is downregulated during congenital obstructive nephropathy, leading to apoptosis. Of great interest, nitric oxide bioavailability associated with heat shock protein 70 (Hsp70) interaction may modulate wt-1 mRNA expression, preventing obstruction-induced cell death during neonatal unilateral ureteral obstruction. Moreover, recent genetic researches have allowed characterization of many of the complex interactions among the individual components cited, but the realization of new biochemical, molecular, and functional experiments as proposed in our and other research labs allows us to establish a deeper level of commitment among proteins involved and the potential pathogenic consequences of their imbalance.